Long-term outcome of oral-aural rehabilitation in patients with cochlear implants - L. A. Lazareva; S. A. Azamatova; S. L. Kovalenko; I. S. Elizbaryan (Кубанский научный медицинский вестник, 2021)
Background. Cochlear implantation is currently the most effective method for oral-aural rehabilitation in children with severe sensorineural hearing loss and deafness. Nevertheless, some controversies remain on timing of surgery and use of mono- and bilateral implants.Objectives. Assessment of the long-term results of oral-aural rehabilitation in children with mono- and bilateral cochlear implants depending on timing of the surgical intervention.Methods. The following oral-aural rehabilitation phases were scored in children with mono-and bilateral cochlear implants: “Language stage of speech perception and production” and “Understanding of coherent speech and complex text”. A retrospective assay used data on 98 patients following long-term oral-aural rehabilitation after cochlear surgery. Command ofmain language components and oral speech was assessed in detail against 12 skill learning criteria by psychoneurologists and teachers of the deaf. Statistical analyses were carried out with MS Office Excel 2010.Results. The “Language stage of speech perception and production” phase long-term scoring in children with bilateral cochlear implants demonstrated the skills of developing auditory memory, active (expressive) vocabulary, dialogic speech and voice control to account for an over 50% improvement in the cohort having had surgery under 3 years of age. In patients with monolateral implants, the additional distinctive skills were aural-visual and aural speech perception and command of coherent speech (over 60% difference vs. the cohort with surgery under 7 years of age). The “Understanding of coherent speech and complex text” phase scoring against three criteria was used to conclude on rehabilitation efficacy after cochlear implantation, approve early surgery and provide further counsel for social adaptation in cochlear implant patients.Conclusion. A comprehensive post-cochlear implant rehabilitation scoring against a number of key criteria provides a more consistent view of oral-aural skill learning. A detailed evaluation of the basic communication tools like command of the main language components and oral speech affirmed the feasibility of bilateral cochlear implantation in children under 3 years of age. The results were used to advance social adaptation in cochlear implant patients.